A Case of Hepatitis E Persistence in a Patient With Myelofibrosis Under Ruxolitinib. Issue 11 (19th November 2021) - Ribeiro da Cunha, Maria; Marques, Tiago
ABSTRACT: Hepatitis E virus (HEV) is a mostly enterically transmitted agent of viral, usually acute hepatitis. In recent years, however, it has been proven to establish chronicity in immunosuppressed patients. We report the first case of HEV infection in a patient with myelofibrosis under ruxolitinib, a tyrosine kinase inhibitor. Although this patient was able to mount a humoral response with specific immunoglobulin G, viral replication could not be controlled until ruxolitinib suspension. After normalization of liver enzymes and clearance of HEV, ruxolitinib was reintroduced with no disease relapse, suggesting spontaneous eradication of the virus.